Detecting atomic-set serializability violations in multithreaded programs through active randomized testing - Lai, Zhifeng; Cheung, S. C.; Chan, W. K. (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
Concurrency bugs are notoriously difficult to detect because there can be vast combinations of interleavings among concurrent threads, yet only a small fraction can reveal them. Atomic-set serializability characterizes a wide range of concurrency bugs, including data races and atomicity violations. In this paper, we propose a two-phase testing technique that can effectively detect atomic-set serializability violations. In Phase I, our technique infers potential violations that do not appear in a concrete execution and prunes those interleavings that are violation-free. In Phase II, our technique actively controls a thread scheduler to enumerate these potential scenarios identified in Phase I to look for real violations. We have implemented our technique as a prototype system AssetFuzzer and applied it to a number of subject programs for evaluating concurrency defect analysis techniques. The experimental results show that AssetFuzzer can identify more concurrency bugs than two recent testing tools RaceFuzzer and AtomFuzzer.